Pengembangan Aplikasi Website Manajemen Gudang: Studi Manajemen Stok dan Harga Per Item di Perusahaan XYZ - Bayu Pamungkas; Erna Haerani (Jurnal Sistem Informasi Galuh, 2026)
This study presents the design and development of a web-based Warehouse Management System (WMS) for Company XYZ using the Agile development methodology. Warehouse operations at Company XYZ previously relied on manual and disconnected processes that produced persistent stock inaccuracies, inconsistent per-item pricing records, and delayed operational reporting. Direct observational data collection was conducted at Company XYZ to elicit functional requirements for two core system modules: stock management and per-item pricing management. The Agile methodology structured development into iterative sprints, enabling continuous user validation of each incremental software release. The resulting web-based application successfully managed real-time stock quantities, unit pricing records, and inventory reports accessible through a centralized browser-based interface. Functional testing confirmed that the application resolved the identified warehouse management deficiencies and demonstrated measurable improvements in data accuracy and operational reporting speed. This research contributes a documented Agile-based development case applicable as instructional material for the Information Systems Department at IPI Garut.